The Influence of Cultural Context in Japan’s Intercultural Negotiations: Analysis of the Drama Nihon Chinbotsu: Kibo no Hito - Febriyani, Lili (KIRYOKU, 2024)
In the Japanese drama titled Nihon Chinbotsu: Kibo no Hito, Japan experienced a major disaster in the form of the sinking of the Kanto region into the ocean. From this disaster, Japan lost land, so its citizens had to be transferred to other countries. Japan is negotiating with various countries to transfer Japanese citizens through the immigration process. This article discusses Japan’s intercultural negotiations with China, the United States, and Australia. The Content Analysis method is used to interpret the film’s content related to Japan's intercultural negotiations with these three countries. By using the theory of Intercultural Communication, this study tries to describe the “cultural context” and values that underlie Japan’s intercultural negotiation process; and analyzes its influence on the negotiation process.From the results of a thorough analysis of the components in the drama, It can be concluded that “cultural context” plays an important role in the negotiation process, and this context is closely related to the distinction between high-context culture and low-context culture. Both high-context and low-context cultures show prominent basic values, which also influence the intercultural negotiation process. These values are (1) collectivism and individualism; (2) the level of intimacy of the relationship between Eastern and Western cultures, which includes uchi-soto, power distance in the social hierarchy, and reciprocal relations; (3) reciprocation (on’gaeshi); which overall affects the negotiation process. In addition, from the analysis, it is concluded that Japan and China have similar values, while the United States has similar values to Australia.